ALCHEMIST BY BEN JONSON - Fayzullayeva Naimaxon Dilshodbek qizi; Kenjaeva Mukhlisa Bakhodir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article describes the life of Ben Jonson and his novel The Alchemist. In addition, this article contains discussions and opinions about the novel The Alchemist.